A tiered, system-of-systems modeling framework for resolving complex socio-environmental policy issues. (February 2019) - Little, John C.; Hester, Erich T.; Elsawah, Sondoss; Filz, George M.; Sandu, Adrian; Carey, Cayelan C.; Iwanaga, Takuya; Jakeman, Anthony J.
Abstract: Many of the world's greatest challenges are complex socio-environmental problems, often framed in terms of integrated assessment, resilience or sustainability. To resolve any of these challenges, it is essential to elicit and integrate knowledge across a range of systems, informing the design of solutions that take into account the complex and uncertain nature of the individual systems and their interrelationships. To meet this scientific challenge, we propose a tiered, system-of-systems modeling framework with these elements: a component-based, software framework that couples a wide range of relevant systems using a modular, system-of-systems structure; a tiered structure with different levels of abstraction that spans bottom-up and top-down approaches; the ability to inform robust decisions in the face of deep uncertainty; and the systematic integration of multiple knowledge domains and disciplines. We illustrate the application of the framework, and identify research and education initiatives that are needed to facilitate its development and implementation. Graphical abstract: Highlights: A generic approach to resolving families of complex socio-environmental problems. Combines a system-of-systems framework with the integrated assessment methodology. Has a tiered structure with different levels of abstraction. Accommodates the need for decision-making in the face of deep uncertainty. Systematically integrates multiple knowledge domains and disciplines.